EUPATI and Patients in Medicines Research and Development: Guidance for Patient Involvement in Regulatory Processes - Haerry, David; Landgraf, Cordula; Warner, Kay; Hunter, Amy; Klingmann, Ingrid; May, Matthew; See, Wolf (Frontiers in Medicine, 2018)
The importance and merits of greater patient involvement in medicines research and development (R&D) are commonly acknowledged and is thought to offer benefits for all involved parties. It improves discovery, development, and evaluation of new effective medicines, based, among others, on the collaborative identification and understanding of unmet needs, research priorities, optimisation of clinical study design, as well as incorporating patient views in regulatory activities. It fosters increased transparency, trust and mutual respect between patients and other stakeholders and applies to all stages of medicines R&D, inclusive of regulation and licensing of medicines and appraisal by health technology assessment (HTA) bodies. In order to be effective and beneficial for all stakeholders, patient engagement as an integral part of medicines R&D needs clear and mutually agreed rules. Existing codes of practice for patient involvement do not comprehensively cover the full scope of patient engagement in all processes related to R&D.. One specific aim of the European Patients’ Academy on Therapeutic Innovation (EUPATI) was to close this gap through the development of guidance documents for pharmaceutical industry-led medicines R&D, ethics committees, regulatory authorities and health technology assessment (HTA). The guidance in this article covers patient involvement in the regulatory field and draws on the mature “Framework for interaction between the European Medicines Agency and patients and consumers and their organisations”. It expands on the EMA framework, specifically including National Competent Authorities (NCAs). It sets out objectives for patient involvement in medicines regulation and recommends concrete suggested working practices. It is primarily aimed at regulatory authorities wishing to interact with patients or their organisations in their activities but should also be considered by patients/patient organisations planning to collaborate with regulatory authorities.